1984
DOI: 10.2527/jas1984.5951303x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Uteroferrin in Placental Iron Transport: Effect of Maternal Iron Treatment on Fetal Iron and Uteroferrin Content and Neonatal Hemoglobin

Abstract: Uteroferrin, an Fe-containing, progesterone-induced glycoprotein is involved in maternal to fetal Fe transport in swine. These studies examined the effect of im Fe injection of dam on conceptus and piglet Fe stores. In Exp. I, eight gilts were bred and assigned to either treatment I (no Fe injections) or treatment II (total of 22 mg iron-dextran/kg body weight on d 40, 45, 50, 55 and 60 of gestation) and hysterectomized on d 90 to determine whether Fe injections increased Fe stores in the conceptus. Total Fe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Nutrients, gases and macromolecules, such as those for transport of iron and vitamins, are transferred from the maternal capillaries into the placental capillaries and then are transported to the heart via the fetal venous system for distribution to all fetal-placental tissues [9,[50][51][52]. All nutrients transferred across the placenta may be cleared via the kidney and into the bladder, from which they can enter the allantoic sac via the urachus for metabolism, degradation, or reuptake into the placental circulation for redistribution to affect development and function of fetal-placental tissues [53].…”
mentioning
confidence: 99%
“…Nutrients, gases and macromolecules, such as those for transport of iron and vitamins, are transferred from the maternal capillaries into the placental capillaries and then are transported to the heart via the fetal venous system for distribution to all fetal-placental tissues [9,[50][51][52]. All nutrients transferred across the placenta may be cleared via the kidney and into the bladder, from which they can enter the allantoic sac via the urachus for metabolism, degradation, or reuptake into the placental circulation for redistribution to affect development and function of fetal-placental tissues [53].…”
mentioning
confidence: 99%
“…Some previous studies have indicated that feeding an organic iron source to pregnant sows increases pig birth weight, fetal iron stores, piglet blood hemoglobin, and reduces postnatal pig mortalities, lowers the number of stillbirths, resulting in heavier weanling weights of pigs (Ducsay et al . ; Close ; Rincker et al . ; Peters & Mahan ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Highest expression of UF mRNA occurs during midto late pregnancy [5]: however, maximal syn thesis and secretion of the corresponding pro tein are observed only at midpregnancy [5,6]. The basis of the partial block in UF mRNA translation during late pregnancy is not un derstood: however, supplementation of mid pregnant gilts with Fe was positively corre lated with accumulation of UF in allantoic fluid [3], suggesting that Fe may enhance UF mRNA translation. The control of UF mRNA synthesis has been partially elucidated in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 92%
“…Transport of Fe from the maternal uterus to the developing fetus during pregnancy in the pig is mediated, in part, by the uterine endometrial protein uteroferrin (UF) [1,2], U F bi nds two atoms of Fe per molecule and is taken up by the fetus via the umbilical vein, subsequent to its release from endometrial glandular epithelium and nonspecific uptake by specialized regions of chorion called areo lae, which overlies each gland [2], Porcine neonates suffer from iron deficiency anemia [3], and it was postulated that this condition may arise in part from a decrease in endome trial UF protein production during late preg nancy [4,5], UF mRNA and protein are tem porally regulated during pregnancy. Highest expression of UF mRNA occurs during midto late pregnancy [5]: however, maximal syn thesis and secretion of the corresponding pro tein are observed only at midpregnancy [5,6].…”
Section: Introductionmentioning
confidence: 99%